Cerebrovascular ageing: how zebrafish can contribute to solving the puzzle - Malkinson, Guy; Henriques, Catarina M. (Frontiers in Physiology, 2025)
The mean life expectancy continues to increase world-wide. However, this extended lifespan trend is not accompanied by health span, or years of healthy life. Understanding the fundamental mechanisms responsible for the switch from health to morbidity with ageing are key to identifying potential therapeutic targets to decrease age-associated morbidity and increase years spent in good health. The leading cause of morbidity in Europe are diseases of the circulatory system and diseases of the nervous system and cognitive disorders are among the top-ten. Cerebrovascular ageing is therefore of particular importance as it links circulatory disease to brain functions, cognition, and behavior. Despite major progress in brain research and related technologies, little is known on how the cerebrovascular network changes its properties as ageing proceeds. Importantly, we do not understand why this is different in different individuals in what concerns rate of dysfunction and its downstream impact on brain function. Here we explore how the zebrafish has evolved as an attractive complementary ageing model and how it could provide key insights to understanding the mechanisms underlying cerebrovascular ageing and downstream consequences.